Comparison of different dose accumulation strategies to estimate organ doses after stereotactic magnetic resonance-guided adaptive radiotherapy - Regnery, Sebastian; Leiner, Lukas; Buchele, Carolin; Hoegen-Saßmannshausen, Philipp; Sandrini, Elisabetta; Held, Thomas; Deng, Maximilian; Eichkorn, Tanja; Rippke, Carolin; Renkamp, Claudia Katharina; König, Laila; Uzun-Lang, Kristin; et al. (Radiation oncology, 2023)
Re-irradiation is frequently performed in the era of precision oncology, but previous doses to organs-at-risk (OAR) must be assessed to avoid cumulative overdoses. Stereotactic magnetic resonance-guided online adaptive radiotherapy (SMART) enables highly precise ablation of tumors close to OAR. However, OAR doses may change considerably during adaptive treatment, which complicates potential re-irradiation. We aimed to compare the baseline plan with different dose accumulation techniques to inform re-irradiation.